Ontology: a support structure for a V-Labs Network, the Euronet - Lab - Correia, Raúl Cordeiro (2014)
This paper presents work on the establishment of a virtual laboratories network, based on the concept of Virtual Closet that will contain all the elements and parts required to build the different experiences available in a vlabs network (that we call Euronet-Lab). To build this complex network it is necessary to find an adequate support. The large database of v-labs and independent elements that can integrate this structure allows the “recycling” of elements for purposes diverse from those they were originally created. This means to “re-use” the same element several times in different scenarios. In order to do this, it is necessary to have a structure that allows multiple instances of the same component. This paper will discuss the ontology essential to the establishment of such a network in order to standardize concepts and create uniform components description that supports the interaction between heterogeneous systems using shared parts or circuits.